2007
DOI: 10.1242/jcs.03364
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 and Rac3 have opposing functions in cell adhesion and differentiation of neuronal cells

Abstract: Overexpression of a neural-specific rho family GTPase, cRac1B, selectively induces enhanced neuritogenesis and neurite branching in primary neurons. J. Cell Biol. 142, 815-825. Amano, M., Ito, M., Kimura, K., Fukata, Y., Chihara, K., Nakano, T., Matsuura, Y.and Kaibuchi, K. (1996). Phosphorylation and activation of myosin by Rho-associated kinase (Rho-kinase).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 61 publications
(58 reference statements)
9
58
1
Order By: Relevance
“…The absence of ERa co-regulatory activity for RAC1 versus RAC3 is another example of the previously observed opposing effects of these two highly homologous proteins (Hajdo-Milasinovic´et al, 2007). In the current study, this difference was mapped to RAC3 S151, which corresponds to A151 in RAC1 (Figure 3).…”
Section: Discussionsupporting
confidence: 46%
“…The absence of ERa co-regulatory activity for RAC1 versus RAC3 is another example of the previously observed opposing effects of these two highly homologous proteins (Hajdo-Milasinovic´et al, 2007). In the current study, this difference was mapped to RAC3 S151, which corresponds to A151 in RAC1 (Figure 3).…”
Section: Discussionsupporting
confidence: 46%
“…Yet, signaling specificity has been, in several studies, clearly linked to the C-terminus of RhoGTPases, both in vitro as well as in vivo. [133][134][135] More recently, several studies have shown for Rac1 that there is a functional connection between the C-terminus and the effector domain in the N-terminus 15 and that some C-terminal interactions are influenced by nuclear import required binding of Karyopherin α2 to the Rac1 C-terminus as well as Rac1 activity, additional factors must control nuclear accumulation of activated Rac1. These may be Rac1 effector domains, but could also be the (mono-)ubiquitylation of Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…Rac3 has not previously been studied in hemopoietic cells, largely because its expression is highest in neurons (Bolis et al, 2003). However, it has previously been shown to have an opposing effect to Rac1 in neuronal cell adhesion and differentiation (Hajdo-Milasinović et al, 2007). Knockdown of RhoGDI1 was recently reported to lead to reduced levels of RhoA, Rac1, and Cdc42 (Boulter et al, 2010).…”
Section: Rhoa Is Required For T Cell Temmentioning
confidence: 99%